2018
DOI: 10.1371/journal.pntd.0006923
|View full text |Cite
|
Sign up to set email alerts
|

Activity profiling of peptidases in Angiostrongylus costaricensis first-stage larvae and adult worms

Abstract: BackgroundAngiostrongylus costaricensis is a relatively uncharacterized nematode that causes abdominal angiostrongyliasis in Latin America, a human parasitic disease. Currently, no effective pharmacological treatment for angiostrongyliasis exists. Peptidases are known to be druggable targets for a variety of diseases and are essential for several biological processes in parasites. Therefore, this study aimed to systematically characterize the peptidase activity of A. costaricensis in different developmental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Other studies have assessed possible functions and applications of the identified proteins by using protein activity assays [ 77 , 93 ] and cloning parasite sequences into plasmids [ 94 ]. A synthetic peptide of the serine/threonine phosphatase 2A (PP2A), an enzyme involved in the embryogenesis and differentiation of A. costaricensis , was tested as a vaccine candidate in murine hosts [ 94 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have assessed possible functions and applications of the identified proteins by using protein activity assays [ 77 , 93 ] and cloning parasite sequences into plasmids [ 94 ]. A synthetic peptide of the serine/threonine phosphatase 2A (PP2A), an enzyme involved in the embryogenesis and differentiation of A. costaricensis , was tested as a vaccine candidate in murine hosts [ 94 ].…”
Section: Introductionmentioning
confidence: 99%
“…This synthetic peptide conferred 60 to 100% protection against A. costaricensis challenge, with a significant increase in IFN-γ and IL-17 levels [ 94 ]. In addition, the proteolytic activity of this worm’s peptides was investigated and showed significant differences among the proteins derived from adult worms and L1 and L3 larvae [ 93 ]. These findings revealed important factors of the complex infection process and promoted different views of potential alternative methods of disease treatment and interruption of life-cycle transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Very few aspartic peptidases were DE, but had high expression in parasitic females and homologues to S. ratti E/S proteins. Aspartic peptidases play a role in haemoglobin digestion in other parasitic helminths, therefore secretion may be linked to feeding within the host gut epithelium where the adult worm resides [74, 75]. We identified a single candidate antigen from the few examined aspartic peptidases which had considerable homology to aspartic proteases from other Strongyloides species, but little to any other relevant species, whereas the full protein had high homology to multiple relevant nematode species including hookworm.…”
Section: Discussionmentioning
confidence: 99%
“…Very few aspartic peptidases were DE, but had high expression in parasitic females and homologues to S. ratti E/S proteins. Aspartic peptidases play numerous roles in parasitic helminths including digestion, immune evasion and tissue invasion, among others linked to feeding within the host gut epithelium where the adult worm resides [81]. We identified a single candidate antigen from the few examined aspartic peptidases which had considerable homology to aspartic proteases from other Strongyloides species, but little to any other relevant species, whereas the full protein had high homology to multiple relevant nematode species including hookworm.…”
Section: Transthyretin-like Proteinsmentioning
confidence: 99%